2012
DOI: 10.1007/s00424-012-1148-1
|View full text |Cite|
|
Sign up to set email alerts
|

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow

Abstract: Both hypoxia and carbon dioxide increase cerebral blood flow (CBF), and their effective interaction is currently thought to be additive. Our objective was to test this hypothesis. Eight healthy subjects breathed a series of progressively hypoxic gases at three levels of carbon dioxide. Middle cerebral artery velocity, as an index of CBF; partial pressures of carbon dioxide and oxygen and concentration of oxygen in arterial blood; and mean arterial blood pressure were monitored. The product of middle cerebral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 37 publications
3
64
3
Order By: Relevance
“…Nevertheless, our findings are in agreement with the above reports, insofar as the trained divers who displayed the largest rise in PETCO 2 during maximal apnoea presented with the greatest impairment in dCA. It is wellestablished that isocapnic hypoxia impairs the cerebral autoregulatory response in awake, spontaneously breathing humans [19][20][21]. It is therefore surprising that we observed no direct relationship between the fall in PETO 2 and the rise in PhSI during maximal apnoea.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, our findings are in agreement with the above reports, insofar as the trained divers who displayed the largest rise in PETCO 2 during maximal apnoea presented with the greatest impairment in dCA. It is wellestablished that isocapnic hypoxia impairs the cerebral autoregulatory response in awake, spontaneously breathing humans [19][20][21]. It is therefore surprising that we observed no direct relationship between the fall in PETO 2 and the rise in PhSI during maximal apnoea.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies indicate that the relationship between arterial CO 2 on cerebrovascular pressure-reactivity is nonlinear, primarily affecting the phase more so than the amplitude dynamics of the cerebral autoregulatory response [15][16][17][18]. Moreover, it is well-established that arterial O 2 tension exerts a modulatory effect on dCA, wherein arterial hypoxaemia seemingly impairs the autoregulatory response [19][20][21]. Consequently, dCA was assessed using phase synchronisation analysis [22,23] on spontaneous, beatto-beat values of mean arterial blood pressure (MAP) and middle cerebral artery blood flow-velocity (CBFV) during maximal apnoea.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the latter factor may account for the overnight changes found in previous investigations; our CVR values calculated from MCAv responses were close to statistical significance for the overnight difference in the hypoxic test CVR values ( Table 2). The overnight changes in conductance CVR were far from statistical significance for both the hyperoxic and hypoxic tests, with conductance CVR in hypoxia significantly greater than in hyperoxia as expected (Mardimae et al, 2012). OSA with its repeated hypoxic episodes might be expected to induce changes in cerebrovascular reactivity, and Morgan et al (2010) found hyperoxic hypercapnic vasodilation in the cerebral circulation was blunted in individuals with sleep-disordered breathing.…”
Section: Discussionmentioning
confidence: 90%
“…When P aO 2 is above 60 mmHg, little vasodilatation is evident (Mardimae et al 2012;Willie et al 2012). Below this threshold, the degree of vasodilatation increases exponentially and outweighs the degree of hypocapnic vasoconstriction A. W. Subudhi and others (Mardimae et al 2012;Willie et al 2012); presumably, to provide greater blood flow in a time of need. While the correlation between changes in gCBF and C aO 2 was not significant, the change in C aO 2 from SL to ALT1 was similar among all subjects and may not have afforded an appropriate range of values to detect the relationship that has previously been shown with progressive haemodilution (Korosue & Heros, 1992).…”
mentioning
confidence: 99%
“…central chemoreception, autonomic nervous system), but all stem from a reduction in P aO 2 (Severinghaus, 2001;Xu & Lamanna, 2006). When P aO 2 is above 60 mmHg, little vasodilatation is evident (Mardimae et al 2012;Willie et al 2012). Below this threshold, the degree of vasodilatation increases exponentially and outweighs the degree of hypocapnic vasoconstriction A. W. Subudhi and others (Mardimae et al 2012;Willie et al 2012); presumably, to provide greater blood flow in a time of need.…”
mentioning
confidence: 99%